Effects of different iron supply to pregnant sows (Sus scrofa domestica L.) on reproductive performance as well as iron status of new-born piglets. Issue 3 (4th May 2017) - Buffler, Marzell; Becker, Christiane; Windisch, Wilhelm M.
ABSTRACT: The present study aimed to investigate the effects of different iron (Fe) supply to sows during gestation on their reproductive performance and placental Fe load. Additionally, the Fe status of the corresponding offspring was assessed. Twenty multiparous sows were fed from insemination to farrowing with isoenergetic and isonitrogenic balanced diets differing in Fe content. The diet low in Fe (Group −Fe) was mainly composed of soybean meal and maize meal and had a Fe content of 114 mg/kg DM. For the diet high in Fe (Group +Fe), the diet was supplemented with Fe(II)SO4 · 7H2 O to a total Fe content of 256 mg/kg. Blood characteristics (haemoglobin, haematocrit, mean corpuscular haem concentration, total Fe-binding capacity, transferrin saturation) of all sows were measured at the beginning and at the end of gestation. Daily Fe retention was calculated at the day of farrowing. After birth, reproductive performance (litter size, piglet weight, litter weight), placental Fe content and Fe blood characteristics of the piglets were determined. Apparent daily Fe retention tended to be greater in Group +Fe ( p < 0.1). Blood parameters of the sows did not show any variations between feeding groups, neither at the beginning nor at the end of pregnancy, whereas placental Fe content was lower in Group −Fe ( p < 0.05). In addition, Fe supply during gestation improved litter size ( p < 0.01) and litter weight ( p < 0.05). Although all sows were supplied according to the current Fe recommendations, a significant decline in reproductive performance of Group −Fe was recognised. Therefore, it was concluded that the re-evaluation of the gross Fe requirements of pregnant sows is inevitable to accommodate the current feeding recommendations.